Optimalisasi Pelayanan Perizinan Berusaha melalui Online Single Submission (OSS) oleh DPMPTSP Kota Padang - Risni, Shafira; Wahyuni, Rahmi; Irfani, Ahmad Zikron; Pribadi, Muhammad Arif; Helmi , Rahmadhona Fitri (CV. ITTC INDONESIA, 2024)
This research aims to examine the implementation of business licensing services through the Online Single Submission (OSS) system implemented by the Investment and One-Stop Integrated Service Office (DPMPTSP) of Padang City. In addition, this research also examines the obstacles faced and solutions applied in optimizing business licensing services. This research is descriptive in nature using qualitative methods. The data sources used are primary data in the form of interviews with the DPMPTSP of Padang City on November 15, 2024 and secondary data derived from laws and regulations and related literature. The data analysis technique was carried out deductively, by reviewing the implementation of the OSS system based on applicable regulations. The results showed that the implementation of business licensing services through OSS by DPMPTSP Kota Padang was in accordance with Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing. OSS provides convenience in the licensing process, which is efficient and electronically integrated. However, the implementation of this system still faces a number of obstacles, including a lack of public understanding, limited access to technology, uneven internet network quality, and technical disruptions due to the transition process to OSS-RBA (Risk-Based Approach). To overcome these obstacles, the DPMPTSP of Padang City provides direct assistance services, education to the community, and intensive coordination with the central government to improve the performance of the OSS system. The results show that although OSS has had a positive impact on the business licensing process in Padang City, optimization of services is still needed to achieve the goal of a more inclusive and competitive bureaucratic reform.